Treatment with neutralising antibody against cytokine induced neutrophil chemoattractant (CINC) protects rats against acute pancreatitis associated lung injury. Issue 6 (1st December 2000) - Bhatia, M; Brady, M; Zagorski, J; Christmas, S E; Campbell, F; Neoptolemos, J P; Slavin, J
Abstract : BACKGROUND: Lung injury manifest clinically as adult respiratory distress syndrome (ARDS) is a common cause of morbidity and mortality following acute pancreatitis (AP). Neutrophils play a critical role in the progression of AP to ARDS. C-x-C chemokines are potent neutrophil chemoattractants and activators and have been implicated in AP. AIMS: To evaluate the effect of blocking the C-x-C chemokine, cytokine induced neutrophil chemoattractant (CINC), in AP on pancreatic inflammation and the associated lung injury in rats. METHODS: AP was induced by hourly intraperitoneal injections of caerulein. Goat anti-CINC antibody was administered either before or after starting caerulein injections to evaluate the prophylactic and therapeutic effects, respectively. Severity of AP was determined by measuring plasma amylase, pancreatic water content, and pancreatic myeloperoxidase (MPO) activity as a measure of neutrophil sequestration in the pancreas. Lung injury was determined by measurement of pulmonary microvascular permeability and lung MPO activity. RESULTS: Treatment with anti-CINC antibody had little effect on caerulein induced pancreatic damage. However, it reduced the caerulein mediated increase in lung MPO activity as well as lung microvascular permeability when administered either prophylactically (lung MPO (fold increase over control): 1.53 (0.21) v 3.30 (0.46), p<0.05; microvascular permeability (L/P%): 0.42 (0.07) v 0.77 (0.11), p<0.05) or therapeutically (lung MPO (fold increase over control): 2.13 (0.10) v 4.42 (0.65), p<0.05; microvascular permeability (L/P%): 0.31 (0.05) v 0.79 (0.13), p<0.05). CONCLUSION: Treatment with anti-CINC antibody afforded significant protection against pancreatitis associated lung injury. These results suggest that CINC plays an important role in the systemic inflammatory response in AP.